Business Diversification in Increasing the Income of Farmer Households - Suci Setiyowati; Yozi Aulia Rahman (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2019)
The aim of this research is identifying the socio-economic condition of farmer households and the development of business diversification, knowing the income of farmer households from business diversification activities and the contribution to income of farmer households, and knowing the level of kindness business of farmer households in the Delanggu District of Klaten Regency. The research data used primary data. The sample of this research was 95 farmer households in Delanggu District. The method of data analysis used quantitative descriptive analysis and entropy index. The results showed that business diversification developed in the horizontal form of rice farming, off farming and non-farm. The average income of respondents from rice farming IDR. 12,914,737, - per year, off farming IDR. 12,906,667, - per year and non-farm IDR. 34,197,095, per year. The level of diversity of the average farmer household business works in 2 types of businesses. The lowest index value was 0.500, with an average 0.754 and a mode 0.693.